The so-called tax anticausalism from realistic causalism - Nieto Guil, Ignacio A. (2023)
The historical dispute between the causalist and anti-causalist doctrine has generated various controversies over the years. In this connection, a part of the doctrine denies the importance of the cause. On the other hand, there are those who defend this position as an essential element. And finally, there are intermediate positions that partially accept it. For this reason, this paper attempts to solve the conflict between those who seek to link the cause as a guiding principle within tax law and, on the contrary, authors who seek to unlink the causal phenomenon, claiming that it would be an extralegal position. Indeed, philosophy as a tool of all valid knowledge lays the foundations of correct thinking to harmonize, within each particular science, the principles that will help give solidity to the set of ideas. Precisely, legal realism is the perfect link between law and the philosophical world to adapt the study of the legal complex to reality, since otherwise, it would fall into a purely systematic position and, therefore, alien to all objectivity, which is always necessary when validating knowledge.